Therapeutic Efficacy of Poly(dl-Lactide-Co-Glycolide)-Encapsulated Antitubercular Drugs against Mycobacterium tuberculosis Infection Induced in Mice - Dutt, Manisha (American Society for Microbiology, 2001)
Poly(dl-lactide-co-glycolide) (PLG) microparticles were developed as carriers for isoniazid and rifampin in order to improve compliance of tuberculous chemotherapy. Antitubercular drugs encapsulated in PLG polymers and injected in a single dose subcutaneously resulted in a sustained release (up to 6 weeks) of drugs in various organs of mice. Further, Mycobacterium tuberculosis H(37)Rv-infected animals given a single shot of chemotherapy in PLG microparticles exhibited a better or equivalent clearance of CFU in various organs compared to those given a daily administration of free drugs.